1995
DOI: 10.1161/01.cir.92.7.1680
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophic Cardiomyopathy

Abstract: HCM is a heterogeneous disease genotypically, phenotypically, pathophysiologically, clinically, and therapeutically. In decisions on the management of these patients, it is important to recognize this heterogeneity and to direct therapy at the predominant abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
197
3
13

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 689 publications
(218 citation statements)
references
References 171 publications
5
197
3
13
Order By: Relevance
“…HCM was diagnosed by established clinical, hemodynamic, and echocardiographic criteria. 13 No significant intraventricular pressure gradient was detected at rest or during provocative maneuvers (the Valsalva maneuver and isoproterenol infusion) after completion of the study protocol in any patient with HCM. The control group consisted of 7 patients undergoing diagnostic cardiac catheterization to evaluate atypical chest pain.…”
Section: Patientsmentioning
confidence: 80%
See 1 more Smart Citation
“…HCM was diagnosed by established clinical, hemodynamic, and echocardiographic criteria. 13 No significant intraventricular pressure gradient was detected at rest or during provocative maneuvers (the Valsalva maneuver and isoproterenol infusion) after completion of the study protocol in any patient with HCM. The control group consisted of 7 patients undergoing diagnostic cardiac catheterization to evaluate atypical chest pain.…”
Section: Patientsmentioning
confidence: 80%
“…cDNA was synthesized from 300 ng of total RNA and human heart total RNA (Clontech) at 42°C for 50 minutes with oligo(dT) [12][13][14][15][16][17][18] and Moloney murine leukemia virus RT (SuperScriptII, Gibco BRL). The DNAse I treatment was carried out in the same reaction mixture as the RT before addition of reverse transcriptase to remove contaminating genomic DNA, as described by Dilworth and McCarrey.…”
Section: Taqman Real-time Quantitative Rt-pcr Analysismentioning
confidence: 99%
“…The clinical course of FHC is highly variable, with a spectrum at presentation that ranges from the asymptomatic carrier state to premature sudden death in childhood. The risk factors for sudden death in FHC include young age at presentation, syncope, myocardial ischemia, inducible sustained ventricular tachycardia during EP study, and a malignant family history (21)(22)(23)(24). In FHC patients who have survived cardiac arrest, electrophysiologic testing has demonstrated that sinus node dysfunction, electrogram fractionation, and inducible ventricular arrhythmias are common (16,25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Management of HCM with midventricular obstruction is difficult and although ventricular septal myotomy -myectomy or dual-chamber (DDD) pacing is the treatment of choice for patients with severe outflow tract obstruction refractory to drug treatment, 5,22 its role in this subgroup of patients with HCM is not yet established. Without other predictors of outcome, except for an outflow gradient no less than 30 mmHg, 23,24 we began treatment with ablocker, although some HCM centers favor verapamil or class Ia antiarrhythmic agents.…”
Section: Discussionmentioning
confidence: 99%